David L. McConnell and Marilyn D. Loveless, Nature and the Environment in Amish Life - Werner, Sarah (Journal for the Study of Religion, Nature and Culture, 2021)
David L. McConnell and Marilyn D. Loveless, Nature and the Environment in Amish Life (Baltimore: Johns Hopkins University Press, 2018), xiv+294 pp., 49.95 (pbk), ISBN: 9781421426167.